PERLINDUNGAN HUKUM BAGI TENAGA KEPERAWATAN DI MASA PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) PADA MASA COVID-19 TERHADAP UPAH LEMBUR YANG DIKONVERSIKAN HARI LIBUR DI RUMAH SAKIT DAERAH MADANI PEKANBARU - Febiola Utami Putri; Rika Lestari; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The density of nurses' working hours during the COVID-19 period, especiallyduring the implementation of PPKM at Madani Hospital, should be clear about theamount of overtime pay for workers in accordance with Law of the Republic of IndonesiaNumber 13 of 2003 concerning Manpower and the Decree of the Minister of Manpowerand Transmigration of the Republic of Indonesia Number KEP.102 /MEN/VI/2004concerning Overtime and Overtime Pay. This thesis research aims to: find out theImplementation of the Fulfillment of Overtime Pay Rights for Nursing Workers during thePPKM Period during the Covid-19 Period at Madani Pekanbaru Hospital and know theLegal Protection for Nursing Workers during the PPKM Period during the Covid-19Period Against Overtime Pay Converted to Holidays at the Madani Pekanbaru Hospital.The type of research used by the author is sociological legal research, because inthis research the author directly conducts research at the location or place under study inorder to provide a complete and clear picture of the problem under study. This researchwas conducted at the Pekanbaru Madani Regional Hospital.The results of the analysis in the study found that: The provision of holidays as aform of